Accelerated Learning Implementation in Memorizing Asmaul Husna using Hanifida Method - Devind Camelia Rossa; Khoirotul Idawati; Hanifudin Hanifudin; Rofiatul Hosna (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2026)
Developing students' interest in memorizing the Asmaul Husna remains a major challenge in Islamic religious education, demonstrating the need for more captivating and effective teaching approaches. This study intends to analyze the implementation of accelerated learning using the Hanifida method for memorizing the Asmaul Husna, examine its educational impact, and identify the factors that support and obstruct its implementation. This study used a qualitative phenomenological approach. Data were collected through interviews, observations, and documentation, and analyzed using data condensation, data display, and conclusion drawing. The results show that the accelerated learning model based on the Hanifida method permits students to memorize the Asmaul Husna more efficiently while increasing their engagement in the learning process. The program likewise enhances memorization fluency, mastery of the Hanifida method, learning discipline, motivation, spiritual development, and self-confidence. Effective teaching strategies, active teacher facilitation, and adequate learning facilities support its successful implementation. However, limited instructional time, the complexity of memorizing numerous Asmaul Husna attributes, and insufficient parental support remain major challenges. The study determines that accelerated learning through the Hanifida method is an effective pedagogical approach for promoting students' interest and achievement in memorizing the Asmaul Husna. These findings have practical implications for improving Islamic religious teaching and contribute to the growing collection of knowledge on innovative memorization strategies.